Dithiocarbamates: Challenges, Control, and Approaches to Excellent Yield, Characterization, and Their Biological Applications. (6th February 2019) - Odularu, Ayodele T.; Ajibade, Peter A.
Abstract : Progresses made in previous researches on syntheses of dithiocarbamates led to increase in further researches. This paper reviews concisely the challenges experienced during the synthesis of dithiocarbamate and mechanisms to overcome them in order to obtain accurate results. Aspects of its precursor's uses to synthesize adducts, nanoparticles, and nanocomposites are reported. Some common characterization techniques used for the synthesized products were assessed. Biological applications are also reported.